2019
DOI: 10.1016/j.anpedi.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Utilidad de la ecografía pulmonar precoz en bronquiolitis aguda leve-moderada: estudio piloto

Abstract: There is a moderate correlation between early lung ultrasound findings with the severity of the AB evaluated by the clinical scales, as well as some relationship with the clinical progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…An observational prospective study by Zoido Garrote et al demonstrated a moderate correlation between LUS findings at hospital admission and the severity of the clinical course, confirming also the higher involvement of the posterior paravertebral and subscapular areas as main severity indexes [ 17 ].…”
Section: Discussionmentioning
confidence: 93%
“…An observational prospective study by Zoido Garrote et al demonstrated a moderate correlation between LUS findings at hospital admission and the severity of the clinical course, confirming also the higher involvement of the posterior paravertebral and subscapular areas as main severity indexes [ 17 ].…”
Section: Discussionmentioning
confidence: 93%
“…Although an association between LUS and bronchiolitis severity was already partially seen in previous studies [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ], they were monocentric and included relatively small samples. More importantly, they included a combination of artifacts, not in line with recent advances in the field of LUS which highlight the potential of the multiple possible artifacts to be used to provide a semi-quantitative assessment of lung disease [ 32 , 33 , 35 , 36 , 38 ].…”
Section: Discussionmentioning
confidence: 98%
“…Exclusion criteria (based on clinical-anamnestic data, not on ultrasound findings), in analogy to the literature [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] were applied rigorously to avoid over fitting: children with immunosuppression, heart diseases, pneumonia (when the clinician according to clinical, laboratory and radiologic data classified the child has having pneumonia rather than bronchiolitis), neuromuscular diseases, cystic fibrosis, bronchopulmonary dysplasia (excluded according to the perinatal history, dependence of oxygen), positive history of foreign body inhalation, unstable critical conditions that required immediate life-saving procedures, and lack of parental consent. No control cases were enrolled because the aim of the study was to compare different stages of clinically diagnosed bronchiolitis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This report is based on deep literature research over the last 20 years with the aim of providing clinical indi- Starting from the knowledge of most common sonographic findings, ultrasound severity scores can be developed to correctly stratify affected children and to predict the clinical course of bronchiolitis; they can also be compared with clinical scores based on the most common symptoms and signs with a reported agreement of 90.6%. LUS allows for the identification of patients in need of supplemental oxygen with high sensitivity and specificity (96.6% and 98.7%, respectively) and correlates with the length of hospital stay [104][105][106][107][108]. According to Bueno-Campana, the identification of at least one consolidation >1 cm in the posterior areas has a relative risk of 4.4 for the need of non-invasive ventilation [109].…”
Section: Discussionmentioning
confidence: 99%